OPTIMASI EKSPRESI MUTAN PETASE PADA ESCHERICHIA COLI BL21 (DE3) PADA SUHU 24OC DAN VARIASI IPTG - Hedi Aldafa, Safero
PET is one type of plastic that is widely used because it is resistant to various physical stresses. These properties then make PET difficult to degrade and become an environmental problem. Ideonella sakaiensis bacteria were found to be able to produce PETase enzymes that can degrade PET. However, these enzymes tend to be unstable at temperatures for industrial degradation. Therefore, the mutant PETase was constructed in silico to become a more stable PETase and higher substrate affinity. This newly designed mutant PETase construct needs to be tested in a wet lab so that it can be expressed and obtain optimal conditions for its expression. This study aimed to determine the optimum duration and concentration of IPTG to express the mutant PETase L117F / Q119Y / S121E / G165A / D186H / R280A / S214H / S238F at 24oC for the presence of activity. The plasmid construct was designed using a PET22b(+) plasmid inserted with a mutant PETase gene with a pelB signal peptide embedded in the upstream region and His-Tag in the downstream region. Plasmids were transformed into host bacteria E. coli BL21(DE3) using the heatshock method and then confirmed using colony PCR, electrophoresis, and DNA sequencing. The optimal condition method was carried out with 8, 16, and 24 hour incubation variations with IPTG concentrations of 0, 0.25, 0.5, and 1 mM. Activity test was carried out using pNPB substrate by measuring absorbance at = 405nm. The results of PCR and DNA sequencing showed that the PETase gene, both mutant and wildtype, had been transformed into E. coli. The results of SDS-PAGE analysis showed that the induction duration of 24 hours and the IPTG concentration of 1 mM produced the thickest protein band among other conditions. This combination was then applied to the mutant PETase activity assay. The enzymatic activity test showed that there was mutant PETase enzyme activity with an average ?absorbance of 0.33253. Further research is needed to characterize the nature and activity of these recombinant enzymes.